The Promotion of Morality and Ethics in Personnel Operation Under Thai Customs - Rachasarn, Maliyaam; Sriram, Narathip; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were: 1) to study the problem in promoting morality and ethics in personnel operation of the Customs Department. 2) to study the causes of problems in promoting morality and ethics in personnel operation of the Customs Department and 3) to propose guidelines in promoting morality and ethics in personnel operation of the Customs Department. This is qualitative research. The data were collected from the relevant sources: primary, secondary, and related research papers. There were 15 key informants who analyzed the descriptive data. The research results were as follows : 1. Found that there are 3 aspects: 1) Obstacles (personnel lacks of responsibility, has corrupt behavior and lacks of service mind. 2) There are 4 problems: (principle problems, procedure, lack of discretion, and roles. 3) moral enhancement: Good governance is adopted as a guideline to enhance morality. 2. Found that 1) caused by 7 causes (1) values, (2) lacking of knowledge, (3) lacking of role models, (4) social change, (5) corruption, (6) conflicts of interest, and (7) participation. 2) There are 2 causal factors which are internal factors: (sorrow, lacking of discipline, necessity leads, emotional pressure, and wrong values.) External factors: (Vices, opportunity for vices, the imbalance between people and work, coercive influence, and lacking of verification). 3. It was found that there were 2 approaches: 1) Personnel must be supplemented in (1) Responsibilities (punctuality cooperation and transparency). (2) Integrity (no conflicts of interest) (3) being a service mind (fast service, non-discrimination, polite speech, politeness) 2) Administration aspects are as follows: 1) duty, 2) Moral enhancement, 3) Knowledge and skill development 4) Civil servant development process. Guidelines for enhancing morality of personnel of the Customs Department, both approaches will lead to a moral organization based on good governance as a guideline that will lead to confidence in service recipients.